Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1991
DOI: 10.1115/91-gt-265
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer in Rotating Serpentine Passages With Trips Normal to the Flow

Abstract: Experiments were conducted to determine the effects of buoyancy and Coriolis forces on heat transfer in turbine blade internal coolant passages. The experiments were conducted with a large scale, multi–pass, heat transfer model with both radially inward and outward flow. Trip strips on the leading and trailing surfaces of the radial coolant passages were used to produce the rough walls. An analysis of the governing flow equations showed that four parameters influence the heat transfer in rotating passages: coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 16 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The rotating ribbed channel studies of Taslim et al [24], Wagner et al [25], and Parsons et al [26] have reported heat transfer results along the channel walls. The flow field in rotating ducts is extremely difficult to analyze due to the rotating domain, but nonetheless it has been done and presented by a few researchers.…”
Section: Review Of Relevant Studiesmentioning
confidence: 99%
“…The rotating ribbed channel studies of Taslim et al [24], Wagner et al [25], and Parsons et al [26] have reported heat transfer results along the channel walls. The flow field in rotating ducts is extremely difficult to analyze due to the rotating domain, but nonetheless it has been done and presented by a few researchers.…”
Section: Review Of Relevant Studiesmentioning
confidence: 99%
“…Many researchers analyzed also the heat transfer in rotating channels with a 180° sharp turn. Wagner et al (Wagner et al, 1991;Wagner et al, 1992), by using a large number of thermocouples, studied the effects of buoyancy and Coriolis forces on heat transfer in turbine blade cooling passages, both with smooth surfaces and with walls roughened by trip strips. With the same technique, some authors (Han et al, 1993;Hsieh and Liu, 1996), analyzed the influence of different heating conditions (uniform wall temperature, or uniform wall heat flux), while others (Dutta and Han, 1996;Al-Hadhrami and Han, 2003) studied the effects of the channel orientation, with respect to the axis of rotation, on the local heat transfer coefficient in two pass, square and rectangular, channels with, and without, ribs.…”
Section: Introductionmentioning
confidence: 99%
“…In examining the published data, as in the present study, the behavior along the leading edge of the inlet duct and that along the trailing edge of the outlet duct has been reported to be more complex than that along the opposite surfaces. Non-monotonic behavior with increasing Ro has been reported with an initial decrease followed by an increase due to centrifugal buoyancy (Wagner et al, 1992), as well as an initial increase followed by a decrease due to changes in the flow pattern (Duna et al, 1996). In the absence of flow data, and the measured details of the complex strongly three-dimensional flow field, only a speculative explanation can be given at this time.…”
Section: Rotation Number Effects At High Reynolds Numbermentioning
confidence: 99%